Pengaruh Inovasi dan Teknologi Informasi Terhadap Perkembangan UMKM Kue Kering dengan Strategi Diversifikasi Sebagai Variabel Intervening - Gusrila Novita Sari; Khairulis Shobirin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this study was to determine the effect of innovation and information technology on the development of Pastries MSMEs with a diversification strategy as an intervening variable. This type of research is field with a quantitative approach. The data source is primary data collected by offline questionnaires to pastry food MSMEs in flatlands, the sample used was 65 MSMEs. The analysis technique using the Stuctural Equation Model is processed using SmartPLS version 4. The results showed that there was no significant effect of innovation and diversification strategies on the development of pastry MSMEs in Tanah Datar. There is a significant influence of innovation on the diversification strategy of pastries in Tanah Datar. There is a significant influence between the Information Technology variable and the development variable of pastry MSMEs in Tanah Datar. There is no significant effect of Information Technology on the diversification strategy variable. Product innovation has no significant effect on the development of MSMEs intervening diversification strategies in Tanah Datar, information technology has no significant effect on the development of MSMEs intervening diversification strategies in Tanah Datar